Septate uterus: incidental finding in multiparous woman with breech with bad obstetric history who had an emergency caesarean - Singh, Shilpi; S. R., Sheela; P. N., Sreeramulu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
The most common anomalies of reproductive tract are Mullerian duct anomalies, among which septate uterus is the commonest with highest reproductive failure rate. As there are some pitfalls in diagnosis therefore the incidence is difficult to be mentioned as many remain asymptomatic. A 20 year old G5P1L0A3 with 36+4 weeks of gestation with breech presentation in active labour came to our hospital. Patient had previous history of intrauterine death at 8 months of amenorrhea and previous abortions at 5, 5 and 4 months of amenorrhoea in the year 2011, 2013, and 2014 respectively. She underwent emergency caesarean section due to breech at 36+4 weeks in active labour with the delivery of a live late preterm female baby extracted by complete breech of weight 2.28kgs with bilateral CTEV of the baby. Intraoperative findings- of septate uterus–septum extending from fundus to external os, fundal dimpling present. Though rare but uterine anomalies should be suspected in patients with recurrent pregnancy loss, preterm birth and malpresentation.